(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The accumulated rich archival material on the musical folklore of the Belgorod region actualizes the problem of the semantic analysis of round dance songs as the dominant genre of the region’s traditional culture. In this work, based on expeditionary materials and researchers’ publications, the choreographic forms of round dances (circular karagods, tanks, figured tanks) of the Belgorod region are identified and described. The general scientific research methods within the framework of comparative, logical and statistical analysis are utilized. The systematic approach to research used in the process of modeling dance culture contributed to the reconstruction of the three-part picture of the world, captured in the dance in many versions.